2021
DOI: 10.1101/2021.08.27.21262264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide meta-analysis and omics integration identifies novel genes associated with diabetic kidney disease

Abstract: Background: Diabetes is the leading cause of kidney disease, and heritability studies demonstrate a substantial, yet poorly understood, contribution of genetics to kidney complications in people with diabetes. Methods: We performed genome-wide association study (GWAS) meta-analyses using ten different phenotypic definitions of diabetic kidney disease (DKD), including nearly 27,000 individuals with diabetes, and integrated the results with various kidney omics datasets. Results: The meta-analysis identified a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Expression of COL18A1 has been associated with human adipocyte differentiation and susceptibility to obesity, and preclinical work demonstrates that knockout of COL18A1 is associated with a reduction in adiposity in murine models [38,39]. A genome-wide meta-analysis linked the COL20A1 gene to diabetic kidney disease [40]. The expression of NT5E has also been associated with the consumption of a high fat diet in preclinical models and, thus, may be associated with obesity [41].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of COL18A1 has been associated with human adipocyte differentiation and susceptibility to obesity, and preclinical work demonstrates that knockout of COL18A1 is associated with a reduction in adiposity in murine models [38,39]. A genome-wide meta-analysis linked the COL20A1 gene to diabetic kidney disease [40]. The expression of NT5E has also been associated with the consumption of a high fat diet in preclinical models and, thus, may be associated with obesity [41].…”
Section: Discussionmentioning
confidence: 99%
“…It plays a major role in adaptive and autoimmunity in the pathogenesis of nephrotic syndrome [ 20 ]. TENM2, which enables signaling receptor binding activity and cell adhesion molecule binding activity, is involved with renal fibrosis and the development of diabetic kidney disease [ 21 ]. TLR2, which plays a fundamental role in pathogen recognition and innate immunity activation, is essential to the pro-inflammatory and detrimental role in the kidney after ischemic reperfusion injury [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, over 2500 genes and 650 proteins have been linked to DKD. Notably, collagen gene COL and its fragments have consistently emerged as significant in multiple studies [145][146][147]. Recent GWAS studies revealed that approximately half of these 2519 genes were upregulated and the other half downregulated in DKD [146].…”
Section: Novel Omics Approaches In Dkdmentioning
confidence: 99%
“…Notably, collagen gene COL and its fragments have consistently emerged as significant in multiple studies [145][146][147]. Recent GWAS studies revealed that approximately half of these 2519 genes were upregulated and the other half downregulated in DKD [146]. At the protein level, out of 678 identified proteins, 279 were upregulated while the remainder were downregulated in DKD [146].…”
Section: Novel Omics Approaches In Dkdmentioning
confidence: 99%
See 1 more Smart Citation